Etika Belajar dan Mengajar pada Tafsir Fathul Qadir Karya Imam Ash Shaukani - Hodijah, Anisa Siti; Ardiansyah (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2023)
Learning and teaching ethics include learning principles and values about what is right and wrong. To explain the ethics of learning and teaching, the basis is Islamic ethics, the Al-Qur'an and As-Sunnah are the main sources. Therefore, researchers want to know the ethics of learning and teaching in the Al-Qur'an. This research uses qualitative methods and literature study in the process. The result is that the application of learning and teaching ethics is the most important part of the learning process. Therefore, both educators and students involved in teaching and learning activities must express respect for each other and maintain ethics. This is clearly based on the Islamic belief that ethics has a very high value so as to create akhlakul karimah. This is also based on the Islamic belief that ethics has a very important value in the world of education. Therefore, by adhering firmly to Islamic education whose orientation is akhlakul karimah, it is hoped that it can produce outstanding teachers and students.